Defect- modulated C, N- ZnO doped ZnS synthesis via self-sacrificial template strategy: A multifunctional platform for environmental applications, and mathematical ecotoxicity profiling evaluation - Simranjit Kaur; Nidhi; Simranjeet Kaur; Deepeka; Shubham Pathak; Sandeep Bansal; Paramdeep Kaur; Sonal Singhal (Journal of Environmental Chemical Engineering, 2026)

Repurposing Coriandrum sativum L. powder into bifunctional graphene oxide decorated biochar material for efficient removal of emerging pollutants and sensing of uranyl ions - Nidhi; Simranjit Kaur; Minakshi; Abhivyakti; Paramdeep Kaur; Sonal Singhal (Bioresource Technology, 2026)

Hierarchal magnetic biochar supported hexagonal layered double hydroxide assemblies: A dual-action platform for sequestration and monitoring of recalcitrant pollutants - Diksha Aggarwal; Abhivyakti; Sandeep Bansal; Sonal Singhal (Process Safety and Environmental Protection, 2026)

Sphenomorphini unravelled: a phylogenomic framework and generic reassessments for Australia’s most species-rich vertebrate radiation - Janne J. Torkkola; Sarin Tiatragul; Elizabeth S. Broady; Ian G. Brennan; J.Scott Keogh; Daniel L. Rabosky; Sonal Singhal; Paul M. Oliver (Molecular Phylogenetics and Evolution, 2026)

Floral waste-derived biochar functionalized with SDS: A bifunctional material for integrated adsorptive removal and fluorescent detection of deleterious pollutants - Minakshi; Diksha Aggarwal; Abhivyakti; Nidhi; Paramdeep Kaur; Sonal Singhal (Process Safety and Environmental Protection, 2025)

Hybrid Zone Analysis Using Coalescent‐Based Estimates of Introgression and Migration in Plateau Fence Lizards ( Sceloporus tristichus ) - Adam D. Leaché; Hayden R. Davis; Sonal Singhal (Molecular Ecology, 2025)
Coalescent modelling of hybrid zones can provide novel insights into the historical demography of populations, including divergence times, population sizes, introgression proportions, migration rates and the timing of hybrid zone formation. We used coalescent analysis to determine whether the hybrid zone between phylogeographic lineages of the Plateau Fence Lizard ( Sceloporus tristichus ) in Arizona formed recently due to human‐induced landscape changes, or if it originated during Pleistocene climatic shifts. Given the presence of mitochondrial DNA from another species in the hybrid zone (Southwestern Fence Lizard, S. cowlesi ), we tested for the presence of S. cowlesi nuclear DNA in the hybrid zone as well as reassessed the species boundary between S. tristichus and S. cowlesi . No evidence of S. cowlesi nuclear DNA is found in the hybrid zone, and the paraphyly of both species raises concerns about their taxonomic validity. Introgression analysis placed the divergence time between the parental hybrid zone populations at approximately 140 kya and their secondary contact and hybridization at approximately 11 kya at the end of the Pleistocene. Introgression proportions estimated for hybrid populations are correlated with their geographic distance from parental populations. The multispecies coalescent with migration provided significant support for unidirectional migration moving from south to north, which is consistent with spatial cline analyses that suggest a slow but steady northward shift of the centre of the hybrid zone over the last two decades. When analysing hybrid populations sampled along a linear transect, coalescent methods can provide novel insights into hybrid zone dynamics.

Leveraging the multifaceted utility of Psidium guajava derived activated carbon: A sustainable strategy for adsorptive detoxification and real-time detection of pollutants in wastewater - Diksha Aggarwal; Harmanpreet Kaur; Paramdeep Kaur; Abhivyakti; Bhupender Singh; Sonal Singhal (Journal of Water Process Engineering, 2025)

Novel heterogeneous magnetically retrievable g-C3N4/ZnO/SrFe12O19 B-type dual Z-scheme heterostructure for recuperated photo-Fenton degradation of organic dye adulterants from wastewater - Twinkle Garg; Simranjeet Kaur; Nitansh; Sonal Singhal (Environmental Science and Pollution Research, 2025)

Progressive waste-to-resource conversion: Synthesizing incense stick ash‑nickel ferrite composites for the pollutant abatement and targeted fluorescence detection of hexavalent chromium - Nitansh; Twinkle Garg; Komal; Simranjeet Kaur; Vinod Kumar; Kulbhushan Tikoo; Sonal Singhal (Journal of Water Process Engineering, 2025)

Palladium‑zinc ferrite varnished hydroxyapatite spherocuboids for electrochemical detection of carcinogenic food preservatives - Jyoti; Deepeka; Paramdeep Kaur; Shweta Rana; Sonal Singhal (Food Chemistry, 2025)

Intercalation of novel Ocimum Sanctum leaves derived carbon dots between g-C3N4/CoFe2O4 Z-scheme heterojunction system for boosting the radicals’ generation in photo-Fenton degradation and synchronized electrochemical sensing of sulfamethoxazole antibiotic - Twinkle Garg; Renu; Nitansh; Vinod Kumar; Kulbhushan Tikoo; Bhupender Singh; Shweta Rana; Sonal Singhal (Process Safety and Environmental Protection, 2024)

Notes from the taxonomic disaster zone: Evolutionary drivers of intractable species boundaries in an Australian lizard clade (Scincidae: Ctenotus ) - Ivan Prates; Mark N. Hutchinson; Sonal Singhal; Craig Moritz; Daniel L. Rabosky (Molecular Ecology, 2024)
Genomic‐scale datasets, sophisticated analytical techniques, and conceptual advances have disproportionately failed to resolve species boundaries in some groups relative to others. To understand the processes that underlie taxonomic intractability, we dissect the speciation history of an Australian lizard clade that arguably represents a “worst‐case” scenario for species delimitation within vertebrates: the Ctenotus inornatus species group, a clade beset with decoupled genetic and phenotypic breaks, uncertain geographic ranges, and parallelism in purportedly diagnostic morphological characters. We sampled hundreds of localities to generate a genomic perspective on population divergence, structure, and admixture. Our results revealed rampant paraphyly of nominate taxa in the group, with lineages that are either morphologically cryptic or polytypic. Isolation‐by‐distance patterns reflect spatially continuous differentiation among certain pairs of putative species, yet genetic and geographic distances are decoupled in other pairs. Comparisons of mitochondrial and nuclear gene trees, tests of nuclear introgression, and historical demographic modelling identified gene flow between divergent candidate species. Levels of admixture are decoupled from phylogenetic relatedness; gene flow is often higher between sympatric species than between parapatric populations of the same species. Such idiosyncratic patterns of introgression contribute to species boundaries that are fuzzy while also varying in fuzziness. Our results suggest that “taxonomic disaster zones” like the C. inornatus species group result from spatial variation in the porosity of species boundaries and the resulting patterns of genetic and phenotypic variation. This study raises questions about the origin and persistence of hybridizing species and highlights the unique insights provided by taxa that have long eluded straightforward taxonomic categorization.

A novel Psidium guajava and Cerium-MOF based dual-responsive bio-composite for the synchronous adsorptive removal and fluorescence detection of tetracycline antibiotics - Diksha Aggarwal; Harmanpreet Kaur; Renu; Twinkle Garg; Abhivyakti; Vinod Kumar; Kulbhushan Tikoo; Bhupender Singh; Anupama Kaushik; Sonal Singhal (Process Safety and Environmental Protection, 2024)

Ultra-sensitive detection and scavenging of arsenic ions and ciprofloxacin using 3D multipurpose hemicellulose based aerogel: Adsorption mechanism and RSM optimization - Kavita Sharma; Manpreet Kaur; Preeti Tewatia; Vijay Kumar; Christian Paulik; Hideaki Yoshitake; Mukta Sharma; Gaurav Rattan; Sonal Singhal; Anupama Kaushik (Bioresource Technology, 2023)

Rational construction of g-C3N4/SnO2/CoFe2O4 dual Z-scheme system as a potential scaffold for fluorescence sensing and visible light driven photocatalytic degradation of lethal pollutants - Twinkle Garg; Renu; Nitansh; Diksha Aggarwal; Vinod Kumar; Kulbhushan Tikoo; Christian Paulik; Anupama Kaushik; Sonal Singhal (Journal of Environmental Chemical Engineering, 2023)

A novel dual-responsive bio-derived magnetic nanocomposite: An excellent catalyst for efficient photodegradation of contaminants and detection of food additive in wastewater - Nidhi; Renu; Twinkle Garg; Jaspreet Kaur; Vinod Kumar; Kulbhushan Tikoo; Anupama Kaushik; Sonal Singhal (Chemical Engineering Journal, 2023)

Bioremediation of multifarious pollutants using laccase immobilized on magnetized and carbonyldiimidazole-functionalized cellulose nanofibers - Kavita Sharma; Preeti Tewatia; Manpreet Kaur; Deepak Pathania; Fawzi Banat; Gaurav Rattan; Sonal Singhal; Anupama Kaushik (Science of The Total Environment, 2023)

Rice straw derived cellulose nanofibers modified with L-histidine for ultra-trace fluorometric assay of Cr(VI) and Hg(II) in aqueous medium - Vijay Kumar; Gaurav Rattan; Preeti Tewatia; Manpreet Kaur; Deepak Pathania; Sonal Singhal; Anupama Kaushik (Journal of Cleaner Production, 2023)

Appraising the electrocatalytic performance of beta-cyclodextrin embellished supramolecular recognition system for pernicious food colorants - Jyoti; Deepeka; Paramdeep Kaur; Vinod Kumar; Kulbhushan Tikoo; Shweta Rana; Sonal Singhal (Analytica Chimica Acta, 2023)

Genetic variability and the ecology of geographic range: A test of the central‐marginal hypothesis in Australian scincid lizards - Sonal Singhal; John Wrath; Daniel L. Rabosky (Molecular Ecology, 2022)
For many species, both local abundance and regional occupancy are highest near the centre of their geographic distributions. One hypothesis for this pattern is that niche suitability declines with increasing distance from a species geographic centre, such that populations near range margins are characterized by reduced density and increased patchiness. In these smaller edge populations, genetic drift is more powerful, leading to the loss of genetic diversity. This simple verbal model has been formalized as the central‐marginal hypothesis, which predicts that core populations should have greater genetic diversity than edge populations. Here, we tested the central‐marginal hypothesis using a genomic data set of 25 species‐level taxa of Australian scincid lizards in the genera Ctenotus and Lerista . A majority of taxa in our data set showed range‐wide patterns of genetic variation consistent with central‐marginal hypothesis, and eight of 25 taxa showed significantly greater genetic diversity in the centre of their range. We then explored biological, historical, and methodological factors that might predict which taxa support the central‐marginal hypothesis. We found that taxa with the strongest evidence for range expansion were the least likely to follow predictions of the central‐marginal hypothesis. The majority of these taxa had range expansions that originated at the range edge, which led to a gradient of decreasing genetic diversity from the range edge to the core, contrary to the central‐marginal hypothesis.

A lizard with two tales: What diversification within Sceloporus occidentalis teaches us about species formation - Ricardo J. Pereira; Sonal Singhal (Molecular Ecology, 2022)
In 1859, Charles Darwin proposed that species are not fundamentally different from subspecies or the varieties from which they evolve. A century later, Dobzhansky (1958) suggested that many such lineages are ephemeral and are likely to reverse differentiation through introgression (Figure 1a); only a few evolve complete reproductive isolation and persist in sympatry. In this issue of Molecular Ecology , Bouzid et al. (2021) showed how new analytical methods, when applied to genomic data, allow us to more precisely determine whether or not species formation follows the paths outlined by Darwin and Dobzhansky (Figure 1b). The authors studied the diversification of the lizard Sceloporus occidentalis , finding a continuum of genetic interactions between the preservation of genetic identity to genetic merger, analogous to what is exemplified by ring species. In doing so, they teach us two tales about species formation: that lineages are fractal byproducts of evolutionary processes such as genetic drift and selection, and that lineages are often ephemeral and do not always progress into fully reproductively isolated taxa. Studying ephemeral lineages like those in S . occidentalis allows us to capture divergence at its earliest stages, and potentially to determine the factors that allow lineages to remain distinct despite pervasive gene flow. These lineages thus serve as a natural laboratory to address long standing hypotheses about species formation.

Predicting speciation probability from replicated population histories - Ivan Prates; Sonal Singhal (Molecular Ecology, 2020)
In this issue of Molecular Ecology , Yamasaki et al. (2020) use genetic data from extensive sampling of Rhinogobius goby fish across the Ryukyu Archipelago in Japan to demonstrate the parallel speciation of a freshwater form from an ancestral amphidromous form. They then show that ecosystem size strongly predicts the probability of speciation between the two forms across islands. In doing so, this study connects population‐level processes (microevolution) to broad‐scale biodiversity patterns (macroevolution), an important but understudied link in evolutionary biology. Moving forward, we can build on this research to (a) more directly determine how geographic, ecological and historical factors influence the different stages of the speciation process, and (b) understand whether mechanisms inferred from insular radiations extend to those on continents, where both demographic histories and environmental regimes are likely more complex.

Glutathione Modified Fluorescent CdS QDs Synthesized Using Environmentally Benign Pathway for Detection of Mercury Ions in Aqueous Phase - Jaspreet Kaur; Komal; Renu; Vinod Kumar; K. B. Tikoo; Sandeep Bansal; Anupama Kaushik; Sonal Singhal (Journal of Fluorescence, 2020)

Is genomic diversity a useful proxy for census population size? Evidence from a species‐rich community of desert lizards - Maggie R. Grundler; Sonal Singhal; Mark A. Cowan; Daniel L. Rabosky (Molecular Ecology, 2019)
Species abundance data are critical for testing ecological theory, but obtaining accurate empirical estimates for many taxa is challenging. Proxies for species abundance can help researchers circumvent time and cost constraints that are prohibitive for long‐term sampling. Under simple demographic models, genetic diversity is expected to correlate with census size, such that genome‐wide heterozygosity may provide a surrogate measure of species abundance. We tested whether nucleotide diversity is correlated with long‐term estimates of abundance, occupancy and degree of ecological specialization in a diverse lizard community from arid Australia. Using targeted sequence capture, we obtained estimates of genomic diversity from 30 species of lizards, recovering an average of 5,066 loci covering 3.6 Mb of DNA sequence per individual. We compared measures of individual heterozygosity to a metric of habitat specialization to investigate whether ecological preference exerts a measurable effect on genetic diversity. We find that heterozygosity is significantly correlated with species abundance and occupancy, but not habitat specialization. Demonstrating the power of genomic sampling, the correlation between heterozygosity and abundance/occupancy emerged from considering just one or two individuals per species. However, genetic diversity does no better at predicting abundance than a single day of traditional sampling in this community. We conclude that genetic diversity is a useful proxy for regional‐scale species abundance and occupancy, but a large amount of unexplained variation in heterozygosity suggests additional constraints or a failure of ecological sampling to adequately capture variation in true population size.

Correction to: Removal of fluoroquinolone from aqueous solution using graphene oxide: experimental and computational elucidation - Sarita Yadav; Neetu Goel; Vinod Kumar; Kulbhushan Tikoo; Sonal Singhal (Environmental Science and Pollution Research, 2018)

Removal of fluoroquinolone from aqueous solution using graphene oxide: experimental and computational elucidation - Sarita Yadav; Neetu Goel; Vinod Kumar; Kulbhushan Tikoo; Sonal Singhal (Environmental Science and Pollution Research, 2018)

Testing hypotheses for genealogical discordance in a rainforest lizard - Sonal Singhal; Craig Moritz (Molecular Ecology, 2012)
Genealogical discordance, or when different genes tell distinct stories although they evolved under a shared history, often emerges from either coalescent stochasticity or introgression. In this study, we present a strong case of mito‐nuclear genealogical discordance in the Australian rainforest lizard species complex of S aproscincus basiliscus and S . lewisi . One of the lineages that comprises this complex, the S outhern S . basiliscus lineage, is deeply divergent at the mitochondrial genome but shows markedly less divergence at the nuclear genome. By placing our results in a comparative context and reconstructing the lineages' demography via multilocus and coalescent‐based approximate B ayesian computation methods, we test hypotheses for how coalescent variance and introgression contribute to this pattern. These analyses suggest that the observed genealogical discordance likely results from introgression. Further, to generate such strong discordance, introgression probably acted in concert with other factors promoting asymmetric gene flow between the mitochondrial and nuclear genomes, such as selection or sex‐biased dispersal. This study offers a framework for testing sources of genealogical discordance and suggests that historical introgression can be an important force shaping the genetic diversity of species and their populations.

Melatonin as a Neuroprotective Agent in the Rodent Models of Parkinson’s Disease: Is it All Set to Irrefutable Clinical Translation? - Naveen Kumar Singhal; Garima Srivastava; Sonal Agrawal; Swatantra Kumar Jain; Mahendra Pratap Singh (Molecular Neurobiology, 2012)